2006
DOI: 10.1039/b607792g
|View full text |Cite
|
Sign up to set email alerts
|

First total synthesis of the 7-oxygenated carbazole alkaloids clauszoline-K, 3-formyl-7-hydroxycarbazole, clausine M, clausine N and the anti-HIV active siamenol using a highly efficient palladium-catalyzed approach

Abstract: Using a convergent palladium-catalyzed construction of the carbazole framework as the key step we have achieved a short synthesis of the 7-oxygenated carbazole alkaloids clauszoline-K, 3-formyl-7-hydroxycarbazole, clausine C (clauszoline-L), clausine M, clausine N and the anti-HIV active siamenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 48 publications
0
75
0
Order By: Relevance
“…Examples using a catalytic amount of Pd and stoichiometric Cu(OAc) 2 or oxygen were also reported. 53 The key step involves a double C-H activation to generate a palladacycle 14 which undergoes reductive elimination to furnish carbazoles. …”
Section: Scheme 36mentioning
confidence: 99%
“…Examples using a catalytic amount of Pd and stoichiometric Cu(OAc) 2 or oxygen were also reported. 53 The key step involves a double C-H activation to generate a palladacycle 14 which undergoes reductive elimination to furnish carbazoles. …”
Section: Scheme 36mentioning
confidence: 99%
“…1). 5 We described the total syntheses of carquinostatin A (1), 6 micromeline (2), 7 siamenol (3) 8 and further prenylated carbazoles using either palladium(II)-catalysed or iron(0)-mediated reactions for construction of the carbazole skeleton. 9 Introduction of the prenyl substituent was achieved by a late-stage cross coupling of the corresponding bromocarbazole with bis-[µ-bromo-(η 3 -1,1-dimethylallyl)nickel] (4).…”
mentioning
confidence: 99%
“…The reaction of 5 with the dimeric nickel complex 4 afforded 3-prenylcarbazole (6) in 80-85% yield. Our first attempts to achieve a palladium(0)-catalysed Stille cross coupling of 5 and tributylprenylstannane (8) resulted mainly in hydrodebromination to carbazole. Screening a variety of ligands, palladium sources and additives, we found that application of Pd(dba) 2 in the presence of tri-tert-butylphosphane and caesium fluoride (cf.…”
mentioning
confidence: 99%
“…However, the regioselectivity of this step is rather poor (the ratio of isomers is 3.8:1; step 1 in Scheme 2). In 2006, Knçlker et al [6] reported a remarkable approach for the general synthesis of clauszoline-K, 3-formyl-7-hydroxycarbazole, clausine-M, clausine-N, clausine-C, and siamenol by utilization of the palladium-catalyzed intermolecular CÀN bond formation between 3-methoxyaniline and 1-bromo-4-methylbenzene, followed by intramolecular C À C bond formation of the coupling product, 3-methoxy-N-p-tolylaniline, as the key step (step 2 in Scheme 2). However, there should be a serious issue of selectivity for this type of cyclization of unsymmetric 3-methoxy-N-p-tolylaniline according to the related previous reports, [7] although it was not discussed in this report.…”
mentioning
confidence: 99%
“…Furthermore, in the first total synthesis of siamenol, [6] the coupling of 3-bromo-6-methyl-9H-carbazol-2-ol required 9.5 equiv of prenyl bromide and 12 equiv of NiA C H T U N G T R E N N U N G (cod) 2 (cod = 1,5-cyclooctadiene) for six days to yield siamenol in 47 % yield with a low purity. Thus, the pure siamenol had to be prepared by preparative HPLC, which makes this method much less attractive.…”
mentioning
confidence: 99%